2018
DOI: 10.1002/2017rs006451
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Sferics: Analysis of the Instantaneous Phase and Frequency Inferred From Complex Waveforms

Abstract: Analysis of very low frequency lightning waveforms, or radio sferics, can contribute to research into lower ionosphere perturbations and the corresponding atmospheric chemistry. Lightning waveforms can also be characterized on the basis of their propagation distance from receivers in order to study radio wave propagation. A bank of average waveforms, that is, the waveform bank, <1,000 km with a spatial resolution of 10 km has been produced, based on the lightning waveforms recorded in Europe on 8 August 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…It is currently not known with certainty whether this phase stability is a property of the causative lightning discharge or a consequence of the electromagnetic wave propagation within the Earth‐ionosphere cavity. However, it is speculated that the distance between the lightning discharge and the array contributes significantly to the observed instantaneous frequencies (Liu et al, ).…”
Section: Measurements Of Phase Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…It is currently not known with certainty whether this phase stability is a property of the causative lightning discharge or a consequence of the electromagnetic wave propagation within the Earth‐ionosphere cavity. However, it is speculated that the distance between the lightning discharge and the array contributes significantly to the observed instantaneous frequencies (Liu et al, ).…”
Section: Measurements Of Phase Stabilitymentioning
confidence: 99%
“…It was recently reported that the instantaneous frequency of lightning pulses implicitly depends on the instantaneous amplitude because the phase is better defined during relative maximum amplitudes when compared to relative minimum amplitudes (Liu et al, ). We extend this analysis here by comparing the instantaneous frequencies of all the measured relative amplitude maxima and minima of the amplitude envelope.…”
Section: Measurements Of Phase Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, lightning researchers often describe radio transmissions as noise (e.g., Füllekrug et al, ; Jacobson et al, ; Smith et al, , and references therein) because anthropogenic radio transmissions limit the detection threshold for natural weak lightning processes such that the influence of disturbing radio transmitters needs to be mitigated. For example, in long‐range lightning detection networks spectral filter techniques are applied to increase the detection efficiency (Dowden et al, ; Liu et al, , , and references therein). When electromagnetic signatures from intermittent lightning discharges and radio transmissions in specific frequency ranges are absent, or removed, small radio signals originating from wave particle interactions in near‐Earth space can be observed at high latitudes and from satellites in space (e.g., LaBelle & Anderson, ; Manninen et al, ; Parrot et al, ; Titova et al, , and references therein).…”
Section: Introductionmentioning
confidence: 99%